La reglamentación de la vida sexual en el islam: interferencia y fusión entre derecho y sexualidad - Katjia Torres (Ambigua, 2014)
This article deals with the interference of Islamic law in sexuality and merging in existing criminal codes of the Islamic Arab states. Analyzingthe legal textsregulatingsexuality inArab-Islamic countries: Islamiccanon law, its main sources-The Qur'ānandthesunna-andexisting criminal codes, it is found thatthecriminalsanctionconsidered illicitsexual prac-tices(zinā)promotesthe restoration, today,twotypes ofcriminaloffensesunder a categorymedieval(ḥudūd), which are sexoutside marriageand homosexuality, around which turnsour study.Analyzingthe legal textsregulatingsexuality inArab-Islamic countries: Islamiccanon law, its main sources-The Qur'ānandthesunna-andexisting criminal codes, it is found thatthecriminalsanctionconsidered illicitsexual practices(zinā)promotesthe restoration, today,twotypes ofcriminaloffensesunder a categorymedieval(ḥudūd), which are sexoutside marriageand homo-sexuality, around which turnsour study. Fromthis analysisit is concluded thatthe interferenceof Islamic lawfavors atwo-speedsexualityin the lightofcourt rulingsin recentyears in severalArab-Islamic countries, whose functionrequiresnovisibledeterrentsuch practices.We addressbrieflythe origin, evolutionof Islamic lawand itspenalcode. Next,trypairing thisencodingwith sexoutside of marriageand homosexualitythrough thearti-clesthat sanctionthese practices.To understandthe significance ofthis measure, we make an approximation of theconceptof sexuality, desire and sexualfreedomcontained inthe sourcesof Islamic law andIslamiclawthe main treaties, from the beginning ofthe implementation of thesha-riatoourdays.We concludeby treating thedeterrent functionof penaliz-ingthese practices,which is none otherthanpromotingsexualityat two speeds: one that requiresreligion andmorality andsociety lives